Penerapan Weighted Aggregated Sum Product Assesment (WASPAS) Pada Pemilihan Kepala Lingkungan Terbaik Medan Kota - Finces Manao, Mignit; Harahap, Ria Zulkarnaen; Hulu, Yuni Kristiani (Universitas Harapan Medan, 2022)
The Chief of Village is an extension of the village head in helping or providing the best service to the community as well as administrative management in the village or other problems. It is only natural for a Chief of Village to be given an appreciation for his performance during his tenure, especially a Chief of Village in the Medan Kota sub-district, before the election of the Chief of Village in the sub-district was very ineffective and efficient and also seemed unfair. Therefore, the selection of the best Chief of Village must use a system to produce accurate values, so that there is no error in the selection of kepling in the Medan Kota sub-district. To overcome the process of selecting the best chip that is experiencing these obstacles by using an application called a Decision Support System.To do the ranking or determine the best neighborhood head using the WASPAS method, this method provides decision makers who make decisions based on the highest ranking or score.